2014
DOI: 10.3389/fnmol.2014.00061
|View full text |Cite
|
Sign up to set email alerts
|

Protein degradation and protein synthesis in long-term memory formation

Abstract: Long-term memory (LTM) formation requires transient changes in the activity of intracellular signaling cascades that are thought to regulate new gene transcription and de novo protein synthesis in the brain. Consistent with this, protein synthesis inhibitors impair LTM for a variety of behavioral tasks when infused into the brain around the time of training or following memory retrieval, suggesting that protein synthesis is a critical step in LTM storage in the brain. However, evidence suggests that protein de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 127 publications
2
88
0
Order By: Relevance
“…At the present time, it is unclear how E 2 might facilitate CA1 spine formation. However, several mechanisms are possible, including inducing post-translational modifications of existing dendritic proteins, altering protein degradation, increasing constitutive protein synthesis, or triggering new protein synthesis, as all of these mechanisms have been implicated in hippocampal memory and/or synaptic plasticity (Holahan and Routtenberg 2007;Klann and Sweatt 2008;Routtenberg 2008;Abbas 2013;Jarome and Helmstetter 2014).…”
Section: Spine Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…At the present time, it is unclear how E 2 might facilitate CA1 spine formation. However, several mechanisms are possible, including inducing post-translational modifications of existing dendritic proteins, altering protein degradation, increasing constitutive protein synthesis, or triggering new protein synthesis, as all of these mechanisms have been implicated in hippocampal memory and/or synaptic plasticity (Holahan and Routtenberg 2007;Klann and Sweatt 2008;Routtenberg 2008;Abbas 2013;Jarome and Helmstetter 2014).…”
Section: Spine Densitymentioning
confidence: 99%
“…Numerous molecules are involved, including neurotransmitter receptors (e.g., NMDA and AMPA), cell-signaling kinases (e.g., ERK, PI3K, PKA, CaMKII, and mTOR), transcription factors, genes, and the enzymes and co-factors that regulate histone acetylation and DNA methylation (e.g., Silva et al 1992;Guzowski and McGaugh 1997;Atkins et al 1998;Impey et al 1998a, b;Schafe et al 1999;Selcher et al 1999;Adams and Sweatt 2002;Wood et al 2005;Horwood et al 2006;Fischer et al 2007;Ploski et al 2008;Guan et al 2009;Lee and Silva 2009;Sweatt 2009;Day and Sweatt 2010;Hoeffer and Klann 2010;Incontro et al 2014;Jarome and Helmstetter 2014;Schoch and Abel 2014;Yiu et al 2014). To examine the roles of these molecules in estrogenic memory modulation, investigators have borrowed a common approach used in neurobiology of learning and memory research in which intracranial infusions of E 2 and inhibitor drugs are combined with posttraining treatments in one-trial learning tasks.…”
Section: Molecular Mechanisms Underlying E 2 'S Effects On Memory Conmentioning
confidence: 99%
“…Published by Elsevier Ltd. All rights reserved. (Frick, 2013;Jarome and Helmstetter, 2014). However, these processes tend to be studied independently and very little is known about the ways in which they interact.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were the first to indicate that the UPS is crucial for the establishment of long-term memory in rats (Lopez-Salon et al 2001). Since then, it has been demonstrated that the inhibition of the proteasome in multiple brain regions results in impairments in memory consolidation (Jarome and Helmstetter 2014).…”
Section: Requirement Of the Ups For Learning And Memorymentioning
confidence: 74%